2019
DOI: 10.1101/683516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza Viruses in Mice: Deep Sequencing Analysis of Serial Passage and Effects of Sialic Acid Structural Variation

Abstract: Influenza A viruses have regularly jumped to new hosts to cause epidemics or pandemics, an evolutionary process that involves variation in the viral traits necessary to overcome host barriers and facilitate transmission. Mice are not a natural host for influenza virus, but are frequently used as models in studies of pathogenesis, often after multiple passages to achieve 30 higher viral titers that result in clinical disease such as weight loss or death. Here we examine the processes of influenza A virus infect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…While replication in cell culture lacks many of the selective pressures found in natural infection, low levels of diversity within the IAV sequences in natural samples have been reported in human, equine and canine infections (Debbink et al., 2017; Valesano et al., 2019; Hoelzer et al, 2010; Murcia et al, 2010). Similar results were seen with the same strains of IAV used in this study when passaged in wild‐type or CMAH ‐/‐ mice (Wasik et al., 2019). Some minority variants arose in individual virus population genomes in our different replicate experiments, in which three virus populations were passaged 5 times in MDCK‐WT or MDCK‐CMAH cells, revealing little variation within populations, but some variation between populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While replication in cell culture lacks many of the selective pressures found in natural infection, low levels of diversity within the IAV sequences in natural samples have been reported in human, equine and canine infections (Debbink et al., 2017; Valesano et al., 2019; Hoelzer et al, 2010; Murcia et al, 2010). Similar results were seen with the same strains of IAV used in this study when passaged in wild‐type or CMAH ‐/‐ mice (Wasik et al., 2019). Some minority variants arose in individual virus population genomes in our different replicate experiments, in which three virus populations were passaged 5 times in MDCK‐WT or MDCK‐CMAH cells, revealing little variation within populations, but some variation between populations.…”
Section: Discussionsupporting
confidence: 88%
“…vRNA was extracted from the stock virus, and from virus populations recovered after passage 1, 5 and 10 and sequenced using Illumina MiSeq. Library generation was performed as previously described (Wasik et al., 2019). In brief, total vRNA was incubated with Superscript III and Platinum Taq‐HiFi (Invitrogen) in the presence of universal influenza amplifying primers (5′ to 3′, uni12a: GTTACGCGCCAGCAAAAGCAGG; uni12b: GTTACGCGCCAGCGAAAGCAGG; uni13: GTTACGCGCCAGTAGAAACAAGG).…”
Section: Methodsmentioning
confidence: 99%
“…Deep sequencing of samples from H7N9-infected patients and their surrounding poultry/environment showed acquisition of the polymerase-enhancing PB2-E627K variation in humans (45). H3N2 and H1N1 growth in mice has been shown to not necessarily proceed through linear accumulation of adaptative mutations (65). Overall, as next-generation sequencing becomes cheaper, faster, and more efficient, real-time monitoring of human-adaptive variations may enable better preparedness for future outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel evolution in the HA gene has previously been observed after passage of influenza A virus in mouse lungs [ 53 ]. More in depth analyses of influenza A viruses passaged in mice demonstrated that single nucleotide variants associated with adaptation were present in all genomic segments [ 22 , 54 ]. Our prior analysis of the HA gene demonstrated parallel evolution in IBV [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small study by Rutvisuttinunt et al, revealed that clinical influenza isolates had more nucleotide diversity than the cultured isolates [ 21 ]. Wasik et al, demonstrated that viruses derived from plasmids also presented as a quasispecies with low levels of variants that didn’t become fixed [ 22 ]. Both antigenic and non-antigenic changes that become fixed can affect viral fitness [ 23 ].…”
Section: Introductionmentioning
confidence: 99%